Drinking Water of Different Salinity Levels and Its Effect on Nutrient Use in Murrah Buffalo Calves - ,, Preeti .; ., N. Kewalramani; ,, Amit Sharma; Kundu, S. S. (Indian Journal of Animal Nutrition, 2018)
Twenty Murrah buffalo male calves of 12-18 months of age were divided into 5 groups of 4 animals each in order to study the influence of saline water on feed intake and nutrient utilization All the animals were fed standard rations comprising of concentrate mixture, green fodder and wheat straw to meet their nutrientrequirements (ICAR, 2013). However, water provided to the animals in control (C), T1, T2, T3 and T4 groups contained 500, 2000, 4000, 6000 and 8000 ppm of total dissolved solids (TDS), respectively. The results revealed that with an increase in the TDS up to 4000 ppm, there was increase in the feed intake and water intake, however, at 6000 and 8000 ppm TDS, there was decrease (P